2012
DOI: 10.1186/1824-7288-38-10
|View full text |Cite
|
Sign up to set email alerts
|

Celiac disease in type 1 diabetes mellitus

Abstract: Celiac Disease (CD) occurs in patients with Type 1 Diabetes (T1D) ranging the prevalence of 4.4-11.1% versus 0.5% of the general population. The mechanism of association of these two diseases involves a shared genetic background: HLA genotype DR3-DQ2 and DR4-DQ8 are strongly associated with T1D, DR3-DQ2 with CD. The classical severe presentation of CD rarely occurs in T1D patients, but more often patients have few/mild symptoms of CD or are completely asymptomatic (silent CD). In fact diagnosis of CD is regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
88
2
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(105 citation statements)
references
References 55 publications
2
88
2
10
Order By: Relevance
“…They found CD in 22 patients [8]. In addition, in accordance with previous studies, they confirmed that CD is more prevalent in female subjects with T1DM than in males [5] and that the age of onset of T1DM is younger in patients with double the disease than in those with diabetes only [6].…”
supporting
confidence: 79%
See 2 more Smart Citations
“…They found CD in 22 patients [8]. In addition, in accordance with previous studies, they confirmed that CD is more prevalent in female subjects with T1DM than in males [5] and that the age of onset of T1DM is younger in patients with double the disease than in those with diabetes only [6].…”
supporting
confidence: 79%
“…For a patient with T1DM, already engaged in coping day by day with a complex chronic disease, the addition of a second 'limiting' condition is probably remarkably difficult. Above all for a child or adolescent, the balance between GFD adherence and daily life is difficult to achieve, and the need to coordinate insulin therapy with proper nutrition and a healthy lifestyle, in order to maintain adequate metabolic control, is already a considerable effort for the young T1DM patient and families [6]. We suggest, however, that the importance of GFD should be stressed for its severe complications such as lymphoma [2], perhaps by ensuring adequate psychological and nutritional support.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In poorly controlled diabetes, excessive renal loss of calcium and magnesium may occur. Coeliac disease occurs in 4-11% of patients with T1DM as opposed to !1% in the general population and should be screened for with serum endomysial antibody assays in those at risk of fracture (91,122,123). If the diagnosis is confirmed with intestinal histology, a gluten-free diet is indicated.…”
Section: Fracture Preventionmentioning
confidence: 99%
“…HLA-DQ8 also confers a risk of type 1 diabetes [4] . Celiac disease affects at least 10% of patients with type 1 diabetes at some point in their lives [5] , with a prevalence that varies between 0.6%-16.4%, according to different studies [6][7][8] . The prevalence of celiac disease among children with type 1 diabetes is significantly higher than in non-diabetic children (in Western countries celiac disease affects around 1%-2% of the non-diabetic population).…”
Section: Introductionmentioning
confidence: 99%